An assessment of sustainable housing affordability in Klang Valley residential areas / Amir Saufi Nozin - Amir Saufi, Nozin (2017)
The steep rise in housing price and rapid development has marginalized part of the population. As a consequence, the provision of affordable housing for the low and middle-income population has always been a hotly debated topic in Malaysia. The current practice of looking at affordability is somehow distorted. Affordable housing shall not be construed merely as short term price-to benefit that focuses too much on price but rather on an interconnectedness, dynamic set of elements within affordability and sustainability measures. Affordability and sustainability have long been defined separately by various schools of thought. Some, however, argue that the two terms go hand in hand, and one cannot exist without the other for effective application to solve this particular housing problem. It is, therefore, the purpose of this thesis to explore the said alternative and presented a viable mean of assessing both terms. In order to achieve the objective(s) of the thesis, a research design was developed to encompass data collection, analysis and interpretation. Secondary data was obtained through an extensive review of past literature in order to reveal all the criteria that can be admissible as contributing to sustainable housing affordability. A total of 44 elements was found to be relevant and were then incorporated into the questionnaire as a primary data tools. The questionnaire basically includes all of the elements divided into 4 of the factors existed under Affordable Housing Schemes (AHS) and Affordable Housing Principles (AHPs) and were dissipated to a sample population of five (5) key locations in the Klang Valley area. The resulting data were then analyzed using IBM SPSS 16.0 software as well as one of the multi-criteria decision making (MCDM) method, namely COPRAS. In addition, inferential statistics was used to illicit information on the reliability, significant and correlational strength of the result respectively. The final result suggests that locations with the highest utility degree, μ are more likely to satisfy the requirement for sustainable housing affordability.